IMPROVING THE QUALITY OF EDUCATION BY IMPROVING WORKING CONDITIONS IN HIGHER EDUCATION INSTITUTIONS - Okhunov, Ravshan Zafarovich; Kadyrov, Muhriddin Kasim (Educational Research in Universal Sciences, 2023)
The article analyzes the issues of improving the quality of education by improving the working conditions of professors and teachers of higher educational institutions in Uzbekistan. In order to improve the quality of education in higher education institutions, it is very important to create favorable working conditions, prevent professors and teachers from unemployment and provide them with permanent employment. Among the strategies of actions that directly contribute to the improvement of the quality of education, the measures aimed at improving the professional skills of teachers and improving their working conditions are very important. The results of the research showed that the better the working conditions of the teaching staff, the higher the quality of their education.